Doctors' unawareness of the drugs their patients are taking: a major cause of overprescribing?. Issue 6513 (11th January 1986) - Price, D; Cooke, J; Singleton, S; Feely, M
Abstract : We studied the accuracy of both hospital and general practitioners' records of current drug treatment in consecutive patients who attended a general medical review clinic. Either the hospital or the general practitioner's records (obtained in a questionnaire), or both, were inaccurate for over 70% of 59 patients interviewed with their medicine. Most of the errors were due to patients taking drugs in addition to those shown in their records. Some of these were inappropriate, and many seemed unnecessary. It appears that neither hospital doctors nor general practitioners are fully aware which drugs their patients are taking, and this may contribute to overprescribing. We believe that considerable financial savings might be made if patients brought all their medicines to every consultation.